Improving Supply Chain Management Efficiency in Fashion: AHP-Based Vendor Selection - Alhamda, Nur Aini; Darmawan, Bambang; Dwiyanti, Vina (Journal Knowledge Industrial Engineering (JKIE), 2024)
In an increasingly competitive industrial world, selecting the right vendor is crucial for maintaining the quality and continuity of a company's operations. This study was conducted at PT Bersama Zatta Jaya Tbk, a company engaged in the Muslim fashion industry, to evaluate and determine the best vendor for the "bergo" product category. The research employed mixed methods, combining both qualitative and quantitative approaches, with primary data obtained through interviews and questionnaires. The data analysis was performed using the AHP (Analytical Hierarchy Process) method. The results of the study indicate that quality is the priority criterion with a weight of 0.43681, making it the main factor in vendor selection. Vendor V1 was selected as the best with a weight of 0.30387, followed by V4, V2, and V3. This study emphasizes the importance of quality in vendor evaluation and provides recommendations for PT Bersama Zatta Jaya Tbk to focus on quality as the primary factor in the vendor selection process.